Attitudes Toward Older People Among Nursing Students in Southeast Asia: A Narrative Review - Suyasa, I Gede Putu Darma; Agustini, Ni Luh Putu Inca Buntari; Sutini, Ni Kadek; Israfil, Israfil; Rittiruang, Amonwan (Adi Husada Nursing Journal, 2025)
The rapid growth of the older population worldwide has had significant consequences in the health care system, especially in preparing prospective nurses as health workers with positive attitudes towards older people. Unfortunately, students' attitudes have been reported to vary from positive attitudes to indications of ageism towards the older age group. This study aimed to identify and describe current findings regarding nursing students' attitudes toward older people in Southeast Asian countries. This study was conducted using a narrative review approach. The literature was sourced from international databases: PubMed, Science Direct, EBSCOhost, and ProQuest. Keywords included "attitude" AND "older people" OR "elderly" OR "older Adult” AND "nursing student". A total of 154 articles were found and there were 7 articles that met the inclusion criteria from five Southeast Asian countries: Indonesia, Malaysia, Thailand, Philippines, and Vietnam. In general, nursing students in the five Southeast Asian countries have positive attitudes toward elderly health and are highly willing to become elderly nurses as their future career. The attitudes toward older people among nursing students are associated with the level of nursing students' knowledge about older people’s health, subjective norms towards older people, perceived behavioral control, good intentions, having learning experiences with project-based learning about older people’s health on campus, and having experience caring for older people during the education process. Incorporating more comprehensive Gerontic nursing content into the nursing education curriculum, including theoretical knowledge and direct practice opportunities, is imperative to increase students’ positive attitude toward older people.